POTENSI DAN PELUANG PENGEMBANGAN HASIL HUTAN BUKAN KAYU DI KPHP MODEL MINAS TAHURA PROVINSI RIAU - Suhesti, Eni; Hadinoto, Hadinoto; Suwarno, Eno (Wahana Forestra: Jurnal Kehutanan, 2017)
This study aims to identify the types of Non-Timber Forest Products (NTFPs) in the KPHP Model Minas Tahura area and analyze the development opportunities to diversify the income of the people around the forest. The research method is survey method, with object of forest area and community around forest. The data taken are primary data, ie vegetation types that have the potential to generate NTFPs and respondent profile data as well as their interests and desires to develop NTFPs. While the secondary data in the form of general conditions KPHP Model Minas Tahura and other data that support. The results of all data are analyzed descriptively. Result of survey and analysis of vegetation found 30 species at the level of trees, While at the pile level found 21 species, the level of sapling 16 species, and the level of seeds as many as 29 species. From all levels of vegetation growth, there are 21 species that potentially produce NTFPs with various functions and benefits, such as food, medicines, and industrial raw materials. The results of interviews and answers to questionnaires from community respondents around the forest, all respondents know NTFPs and are eager to develop various types of NTFPs in forest areas. It can be concluded that KPHP Model Minas Tahura area has the potential to develop NTFPs based on the availability of critical land for rehabilitation with various types of plants and the desire of surrounding communities to get involved in such activities.